Correction: Cisplatin-induced epigenetic activation of miR-34a sensitizes bladder cancer cells to chemotherapy - Li, Heng; Yu, Gan; Shi, Runlin; Lang, Bin; Chen, Xianguo; Xia, Ding; Xiao, Haibing; Guo, Xiaolin; Guan, Wei; Ye, Zhangqun; Xiao, Wei; Xu, Hua (Molecular cancer, 2022)
[RAW_REF_TEXT] Correction [/RAW_REF_TEXT] [RAW_REF_TEXT] Open Access [/RAW_REF_TEXT] [RAW_REF_TEXT] Published:28 July 2022 [/RAW_REF_TEXT] Correction: Cisplatin-induced epigenetic activation of miR-34a sensitizes bladder cancer cells to chemotherapy [RAW_REF_TEXT] Heng Li1 na1, [/RAW_REF_TEXT] [RAW_REF_TEXT] Gan Yu1 na1, [/RAW_REF_TEXT] [RAW_REF_TEXT] Runlin Shi1, [/RAW_REF_TEXT] [RAW_REF_TEXT] Bin Lang3, [/RAW_REF_TEXT] [RAW_REF_TEXT] Xianguo Chen4, [/RAW_REF_TEXT] [RAW_REF_TEXT] Ding Xia1, [/RAW_REF_TEXT] [RAW_REF_TEXT] Haibing Xiao1, [/RAW_REF_TEXT] [RAW_REF_TEXT] Xiaolin Guo1, [/RAW_REF_TEXT] [RAW_REF_TEXT] Wei Guan1, [/RAW_REF_TEXT] [RAW_REF_TEXT] Zhangqun Ye1, [/RAW_REF_TEXT] [RAW_REF_TEXT] Wei Xiao 2 & [/RAW_REF_TEXT] [RAW_REF_TEXT] Hua Xu 1 [/RAW_REF_TEXT] Molecular Cancer volume 21, Article number: 155 (2022) Cite this article [RAW_REF_TEXT] 146 Accesses [/RAW_REF_TEXT] [RAW_REF_TEXT] Metrics details [/RAW_REF_TEXT] Correction: Mol Cancer 13, 8 (2014) https://doi.org/10.1186/1476-4598-13-8 Following publication of the original article [1], an error was identified in the images presented in Fig. 4, specifically: F Relative miR-34a expression in xenografts; G) Photographs of tumors excised 38 days after inoculation of stably transfected cells into nude mice; Mean xenograft tumor volume H) and weight I) in nude mice groups after indicated treatment (mean + SEM; n = 3; *p < 0.05) Full size image Figure 4B: incorrect images were originally used for Lenti-NC in 5637 cell line; the correct images are now used Furthermore, two of the primer sequences listed in the Table S1 (part of ‘Additional file 3: Correction Open Access Published:28 July 2022 [/RAW_REF_TEXT] Correction: Cisplatin-induced epigenetic activation of miR-34a sensitizes bladder cancer cells to chemotherapy [RAW_REF_TEXT] Heng Li1 na1, Gan Yu1 na1, Runlin Shi1, Bin Lang3, Xianguo Chen4, Ding Xia1, Haibing Xiao1, Xiaolin Guo1, Wei Guan1, Zhangqun Ye1, Wei Xiao 2 & Hua Xu 1 [/RAW_REF_TEXT] Molecular Cancer volume 21, Article number: 155 (2022) Cite this article [RAW_REF_TEXT] 146 Accesses Metrics details